The delightful horror of family birding : sharing nature with the next generation - Knapp, Eli J. (Torrey House Press, 2018)
"Eli Knapp takes readers from a leaky dugout canoe in Tanzania and the mating grounds of Ecuador's cock-of-the-rock to a juniper titmouse's perch at the Grand Canyon and the migration of hooded mergansers in a New York swamp, exploring life's deepest questions all along the way. In this collection of essays, Knapp intentionally flies away from the flock, reveling in insights gleaned from birds, his students, and the wide-eyed wonder his children's experience. The Delightful Horror of Family Birding navigates the world in hopes that appreciation of nature will burn intensely for generations to come, not peter out in merely a flicker. Whether traveling solo or with his students or children, Knapp levels his gaze on the birds that share our skies, showing that birds can be a portal to deeper relationships, ecological understanding, and newfound joy."--Amazon.com.